A novel ozone gas sensor based on one-dimensional (1D) alpha-Ag2WO4 nanostructures - Silva, Luis F. da [UNESP]; Catto, Ariadne C.; Avansi, Waldir; Cavalcante, Laecio S.; Andres, Juan; Aguir, Khalifa; Mastelaro, Valmor R.; Longo, Elson [UNESP] (Royal Soc Chemistry, 2014)
This paper reports on a new ozone gas sensor based on alpha-Ag2WO4 nanorod-like structures. Electrical resistance measurements proved the efficiency of alpha-Ag2WO4 nanorods, which rendered good sensitivity even for a low ozone concentration (80 ppb), a fast response and a short recovery time at 300 degrees C, demonstrating great potential for a variety of applications.